Community Service-Based Analysis of the Communication Role of Information Service Staff in Improving Patient Complaint Management at Muhammadiyah Hospital Palembang - Efrizal Ariansyah (CV. Doki Course and Training, 2025)
This article presents the results of a community service program aimed at enhancing patient complaint management services through improved communication practices by information service staff at Muhammadiyah Hospital Palembang. The program was conducted as part of the university's community engagement mission to support healthcare institutions in strengthening service quality. The method involved participatory training, simulation, and mentoring sessions focusing on communication ethics, active listening, and systematic complaint management. The evaluation results showed an improvement in staff communication competencies and increased patient satisfaction following the program. This activity highlights the strategic role of community service programs in addressing service gaps within healthcare institutions